Assessment of Wave Energy in the South China Sea Based on GIS Technology - Gang Lin; Long Tan Shao; Chong Wei Zheng; Xiao Bin Chen; Li Feng Zeng; Zhi Hong Liu; Rong Bo Li; Wei Lai Shi (Advances in Meteorology)
China is now the world’s largest user of coal and also has the highest greenhouse gas emissions associated with the mining and use of coal. Under today’s enormous pressures of the growing shortage of conventional energy sources and the need for emission reductions, the search for clean energy is the most effective strategy to address the energy crisis and global warming. This study utilized satellite remote sensing technology, geographic information system (GIS) technology, and simulated wave data for the South China Sea. The characteristic features of the wave energy were obtained by analysis through the wave resource assessment formula and the results were stored in a GIS database. Software for the evaluation of wave energy in the South China Sea was written. The results should provide accurate, efficient references for wave energy researchers and decision-makers. Based on a 24-year WW3 model simulation wave data and GIS technology, this study presented the characteristic of the wave energy in the SCS; results demonstrated that the SCS has the feasibility and viability for wave energy farming.